Recuperação de palinomorfos e dados isotópicos (?13 C e ?15N) em sedimentos turfosos e seu significado paleoambiental para a região de Campo Mourão - Ladchuk, Daiane Patrícia Pulcinelli Tavares (2016)
The first paleoenvironmental studies using bioindicators about the origin of the Campo Mourão Cerrado have done the recovery, identification and quantification of phytoliths in a sedimentary core (110 cm of depth). The core was obtained using the vidro-core system in a peat bog located in the Água dos Papagaios river plain near the urban area. Considering the occurrence of pollen grains in this same material we studied it using the paleopalynology techniques with the support of isotopic values (13C and 15N). The city of Campo Mourão is situated in a transitional zone between the Araucaria Forest and the Semidecidual Forest with presence of enclaves of Cerrado. The analyzed material was dated (14C) in the depth 75 cm (7280 cal yrs BP) and 45 cm (3248 cal yrs BP). For the pollinic recuperation was used the standard methodology in 28 samples intervals distributed along the core. For each intervals were prepared 5 microscope slides and 3 of them were used for absolute counting of palynomorphs (pollen grains and spores). We identified 35 botanic families. The major occurrence was spores of pteridophytes, bryophytes and algae (all Pseudoschizeae) summed values above 50%, followed by pollen of herbaceous plants and arboreal/shrubby vegetation. The15N values indicated mixture of terrestrial and aquatic plants along the profile. The pollinic concentration was low (<400 grains of angiosperm and gymnosperm), although considering the quantification allied with the spores counting and isotopic values we established 3 paleoenvironmental phases: Phase I (110 to 75 cm depth), dated at the top in 7280 cal yrs BP, it is characterized by greater palynomorphs preservation (218-1098 grains), 6% of shrubby/arboreal pollen grains, 42% grains of herbaceous pollen and 52% of spores (bryophytes and pteridophytes) and 16% algae spores - highlighting the record of Caryocariaceae and Araucariaceae pollen grains - the 13C values indicated predominance of C4 plants; Phase II (75 to 45 cm depth), dated at the top in 3248 years has palynomorph concentration between 196-442 grains and presents 3% of shrub/tree pollen, 33% of herbaceous pollen grains, 49% spores (bryophytes and pteridophytes) and 14% algae spores - the 13C values indicated mixture between C3 and C4 plants (tendence to C4); Phase III (45 to 0 cm depth) presents the lowest concentration of palynomorphs (13-547 grains); 3% of shrubby/arboreal pollen, 43% of herbaceous pollen grains, 45% spores (bryophytes and pteridophytes) and 9% algal spores - the 13C values indicating isotopic depletion but it still under condition C4. Phases I and II can be interpreted as having a drier climate than the current conditions, however the lower palynomorphs preservation in the phase III and the probable human interference in the area does not provide enough information for a paleoenvironmental characterization. The occurrence of Caryocaraceae pollen grains combined with13C data, relative the C4 plants, highlights the existence of Cerrado in the region of Campo Mourão since the middle Holocene. Considering that its presence is detected from the base of the sedimentary profile we assume that such occurrence extends to the late Pleistocene. The presence of Araucariaceae pollen grains shows that the Cerrado vegetation in the study area could be conditioned to spots surrounded by Araucaria Forest since middle Holocene. The interpretations established in this research supports the previous paleoenvironmental reconstruction using phytoliths analysis that also indicated drier phases during the Holocene. Such combination of different proxy data open new perspectives for future studies in paleoenvironmental interpretation where pollen or phytoliths preservation is not satisfactory